Change in coke characteristics in a low-movement coke bed of blast furnaces - Kriachko , H.Yu.; Siharov , Ye.M. (Theory and Practice of Metallurgy, 2025)
The question of the appropriateness of using the archaic term “tooterman” in relation to the relatively immobile coke mass in the lower part of blast furnaces was raised. For the first time, an attempt was made to summarize information about changes in coke characteristics depending on its location in local MCM zones, for which a conditional division of the MCM into three interdependent but functionally different parts: the upper central superheater (feeding), the middle part between the air blast and cast iron nozzles (working), and the lower part located in the sump (MKM working zone). The conditions for the use of coke in local parts of the MCM were comprehensively considered. New data about the increase in melting intensity on the size of the living part of the MCM has been extracted. It has been shown that the very changes in the intensity of smelting are done to ensure the life of the tuyere part by heating with coke. It is shown by comparing the structure of the MCM of two Japanese blast furnaces cooled during operation that working at a reduced smelting intensity leads to the degeneration of the stable axial zone of low-mobility materials above the tuyere horizon, thereby changing the conditions for preliminary coke heating and its supply to the lower parts of the MCM. The known mechanism of coke piece destruction by liquid metal flowing past them with carbonization of the latter needs to be clarified, since liquid slag formed on the tuyeres during oxidation of Fe, Si, Mn, and P components of cast iron also moves through the sub-tuyere coke mass, The restoration of these oxides requires additional consumption of coke carbon. Based on the generalization of research data and theoretical principles of the blast furnace process, the sequence of coke combustion processes in the MCM sub-bed array is proposed. The mechanism of erosive influx onto the coke massif, which is located in the zone of intense molten flow, has been clarified. It is shown that in this array, there is not one process of coke consumption for metallurgical reactions, as previously thought, but three. The influence of MCM “survivability” on the technical and economic indicators of smelting has been assessed.